2014
DOI: 10.4018/978-1-4666-5154-8.ch029
|View full text |Cite
|
Sign up to set email alerts
|

Managing Customer Knowledge in Service Economy

Abstract: In the age of service and knowledge economy, firms have realized that obtaining, managing, and sharing customer knowledge can be a valuable resource to have advantages over their competitors. However, the review of the literature of Customer Knowledge Management (CKM) area suggests that firms often fail in applying the true notion of CKM, thinking it only as a new technological innovation related to IT. Moreover, the terms Knowledge Management (KM), Customer Relationship Management (CRM), and Customer Knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The use of social media as a source of knowledge for CKM is still small; however, it is already a reality (Sedighi et al , 2012; Chaves et al , 2014; Pandey et al , 2014; Del Vecchio et al , 2018b, 2020) and is something that reinforces the correlation between CKM and STDs. Our review found that CKM is a widely discussed topic and several studies reinforce the importance of building conceptual CKM structures, as the number of structures that detail their processes, activities, methods, techniques, tools (MTFs) and actors involved is still low.…”
Section: Results From the Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of social media as a source of knowledge for CKM is still small; however, it is already a reality (Sedighi et al , 2012; Chaves et al , 2014; Pandey et al , 2014; Del Vecchio et al , 2018b, 2020) and is something that reinforces the correlation between CKM and STDs. Our review found that CKM is a widely discussed topic and several studies reinforce the importance of building conceptual CKM structures, as the number of structures that detail their processes, activities, methods, techniques, tools (MTFs) and actors involved is still low.…”
Section: Results From the Systematic Reviewmentioning
confidence: 99%
“…Lopez-Nicolas and Molina-Castillo (2008) consider CKM an external perspective of knowledge management (KM) capable of contributing to the absorptive capacity of organizations and improving the relationship between clients and organizations. As a result of its contributions, several authors consider CKM a result of the integration between customer relationship management (CRM) and KM, focusing on KM’s thoughts to deepen the functions of CRM by improving the understanding of customers’ needs, demands and behaviors (Skotis et al , 2013; Pandey et al , 2014; Gohary and Hamzelu, 2016; Sachamanorom and Senoo, 2016; Smith and Charles, 2018; Khosravi and Hussin, 2016).…”
Section: Customer Knowledge Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this underperformance, companies should be more open to external knowledge sources that help to boost innovation performance (Caputo, Lamberti, Cammarano, & Michelino, 2016) and reallocate traditionally separated tasks into new forms of horizontal stakeholder collaborations (Kortmann & Piller, 2016). Furthermore, they have realized that obtaining, managing, and sharing consumer knowledge can be a valuable resource to create innovations and maintain their market competitiveness (Pandey, Shukla, & Maurya, 2014). More and more companies are putting customers at the heart of their innovation efforts and encourage them to share knowledge, engage in business processes, and create innovations (Deloitte, 2018).…”
Section: Introductionmentioning
confidence: 99%